PENGARUH PENGEMBANGAN KARIR DAN PENEMPATAN KERJA TERHADAP PRESTASI KERJA KARYAWAN PT, BANK PEMBIAYAAN RAKYAT SYARIAH RAHMAH HIJRAH AGUNG DI KOTA LHOKSEUMAWE - Ikhsan, Muhammad; Nursanjaya, Nursanjaya (Program Studi Administrasi Bisnis, 2022)
This research aims to determine the influence of career development and work placement on the work performance of PT employees. Rahmah Hijrah Agung Lhokseumawe City. This research was conducted on PT. Rahmah Hijrah Agung Lhokseumawe City. This study used primary data in the form of questionnaires distributed to PT employees. Rahmah Hijrah Agung Lhokseumawe City as many as 36 respondents. The data analysis methods used are instrument tests and classical assumption tests as well as multiple linear regression tests using the help of SPSS version 26 software. The results of the partial testing showed that career development did not have a significant effect on employee work performance, while work placement had a positive and significant effect on the work performance of PT employees. Rahmah Hijrah Agung Lhokseumawe City. Meanwhile, from the results of simultaneous testing it was obtained that career development and work placement together had a significant effect on the work performance of PT employees. Rahmah Hijrah Agung Lhokseumawe City.